2016
DOI: 10.17221/708/2015-pse
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the content of various Fusarium mycotoxins forms in germinating winter wheat and spring barley kernels

Abstract: Fusarium mycotoxins are frequent contaminants in cereals at temperate zone. Next to deoxynivalenol (DON), there are other masked forms of DON, deoxynivalenol-3-glucoside (D3G) or 3(15)-acetyl-deoxynivalenol (3(15)-ADON), but changes among these forms are still insufficiently known. All these forms were evaluated in germinating kernels of wheat and malting barley from deliberated inoculated field plots. Results showed possible occurrence of high initial content of all evaluated DON forms. Total contents of all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Next to DON, there are other masked forms of DON, deoxynivalenol-3-glucoside (D3G) or 3(15)-acetyldeoxynivalenol (3(15)-ADON), but changes among these forms are still insufficiently known (Maresca, 2013). Pazderu et al (2016) suggested high importance of evaluating not only DON, but all DON forms simultaneously. Fusarium head blight tolerant cultivars may contain a high proportion of grain which is apparently healthy, but contain excessive DON levels.…”
Section: Resultsmentioning
confidence: 99%
“…Next to DON, there are other masked forms of DON, deoxynivalenol-3-glucoside (D3G) or 3(15)-acetyldeoxynivalenol (3(15)-ADON), but changes among these forms are still insufficiently known (Maresca, 2013). Pazderu et al (2016) suggested high importance of evaluating not only DON, but all DON forms simultaneously. Fusarium head blight tolerant cultivars may contain a high proportion of grain which is apparently healthy, but contain excessive DON levels.…”
Section: Resultsmentioning
confidence: 99%
“…Experimental determination of the concentration of mycotoxins is quite complicated. Moreover, it is infl uenced by processes occurring inside the seed and varies with time (Pazderů et al, 2016;Maul et al, 2012;Wolf-Hall, 2007). Detailed analysis of the transfer of fi ve Fusarium toxins -deoxynivalenol (DON), HT-2 toxin (HT-2), zearalenone (ZON) and sum of 15-and 3-acetyl-deoxynivalenol (ADONs) -from fi eld barley through malt to beer was investigated in detail by K. Lancova and co-workers (Lancova et al, 2008).…”
Section: Effect Of Plasma On Fungi and Mycotoxinsmentioning
confidence: 99%